Consult, Negotiate, and Involve: Evaluation of an Advanced Communication Skills Program for Health Care Professionals. (July 2018) - Coad, Jane; Smith, Joanna; Pontin, David; Gibson, Faith
Effective communication is central to children, young people, and their families' experiences of health care. Most patient complaints in developed health care systems result from ineffective communication, including inadequate information provision, not feeling listened to, failure to value patients concerns, and patients not feeling involved in care decisions. Advanced communication skills training is now embedded within cancer care policy in the United Kingdom and now features prominently within cancer education in many countries. Here, we share findings from a research evaluation of an advanced communication skills training program dedicated to health professionals caring for children and young people with cancer. We evaluated participants' (n = 59) perceptions of the program, impact on their skills, knowledge, competence, and confidence. An appreciative inquiry design was adopted; data included interviews, precourse-postcourse evaluations, e-mail blog survey, and 360-degree reflective work records. The framework approach underpinned data analysis and triangulation of data sets. Key findings highlighted good and poor practice in health professionals' engagement with children, young people, and their families; the purpose of communicating effectively was not always consistent with collaborative working. Attending a program helped participants expand their knowledge of communication theories and strategies. Participants valued using simulated scenarios to develop their skills and were keen to use their new skills to enhance care delivery. Our emphasis within this evaluation, however, remained on what was communicated, when and how, rather than to what effect. The impact of programs such as these must now be evaluated in terms of patient benefit.